Stimullus, Capability, Ego, and Fraudulent Financial Statement: The Role of Audit Quality - Helmiansyah Irawan; Fidelia Ifeyinwa Nzekwe Chinwuko; Khomsiyah; Titik Aryati (Journal of Economic Education and Entrepreneurship Studies, 2026)
Financial statement fraud remains a critical issue that threatens corporate transparency and investor confidence. This study aims to examine the influence of stimulus, capability, and ego on fraudulent financial statements and to analyze the moderating role of audit quality. The research is based on the Fraud Hexagon Theory, Agency Theory, and Positive Accounting Theory, which explain how managerial pressure, authority, and behavioral characteristics may influence financial reporting manipulation. The study uses panel data from non-financial companies listed on the Indonesia Stock Exchange during the 2023–2024 period. A total of 344 firm-year observations were analyzed using purposive sampling. The data were analyzed using Moderated Regression Analysis (MRA) with panel data estimation. The results indicate that stimulus and capability have a positive and significant effect on fraudulent financial statements, suggesting that financial pressure and managerial authority increase the likelihood of financial reporting manipulation. However, ego does not significantly influence fraudulent financial statements. Furthermore, audit quality is found to weaken the positive relationship between stimulus and fraudulent financial statements, indicating that high-quality audits can mitigate the impact of financial pressure on fraudulent reporting behavior. However, audit quality does not significantly moderate the relationship between capability and ego with fraudulent financial statements. This study contributes to the fraud literature by providing empirical evidence on the role of fraud determinants and audit quality in explaining fraudulent financial reporting in emerging markets.